PTH-009 Nicevis – results of a randomised controlled trial of simeticone and n-acetylcysteine as a pre-procedure drink to improve mucosal visibility during diagnostic gastroscopy. (22nd June 2015) - Basford, PJ; Brown, J; Gadeke, L; Fogg, C; Haysom-Newport, B; Ogollah, R; Higgins, B; Bhattacharyya, R; Longcroft-Wheaton, G; Thursby-Pelham, F; Neale, J; Bhandari, P
Abstract : Introduction: Despite advances in endoscope technology there is still a significant miss rate of neoplastic lesions during gastroscopy. Mucosal views are frequently impaired by residual bubbles and mucus. Method: We conducted an RCT in 126 patients attending for routine gastroscopy. Subjects were randomised in a 1:1:1 ratio to receive a pre-procedure drink of water, simeticone and n-acetylcysteine (Group A), water alone (Group B) or no preparation (Group C). Study endoscopists were blinded to group allocation. 4 digital images were taken at pre-defined locations during the procedure – lower oesophagus, upper body, antrum and fundus. Images were rated for mucosal visibility (MV) using a 4 point scale (1 = best, 4 = worst) by 4 blinded experienced endoscopists. Primary outcome measure was mean MV score. Secondary outcome measures were procedure duration and volume of flush required to achieve adequate mucosal views. Results: Groups were well matched for age, gender or indication for endoscopy. Mean MV score for group A was significantly better than for group B and group C (p < 0.001 for both comparisons), with no significant difference between groups B and C (p = 0.541). Interobserver agreement of MV scores was good (mean kappa 0.464). Mean volume of flush required to achieve adequate mucosal views was significantly lower in group A than group B (p = 0.001), and group C (P < 0.001). There was no significant difference in mean flush volume between groups B and C (p = 0.583). Procedure duration did not differ significantly between the groups. Subgroup analysis of MV scores at each location demonstrated significantly better mucosal visibility in group A compared to group B and group C at all locations (p < 0.0025 for all comparisons). Conclusion: A pre-procedure drink containing simeticone and n-acetlycysteine significantly improves mucosal visibility during routine gastroscopy and reduces the need for flushes during the procedure. This may improve detection of early neoplasia and other pathology during gastroscopy. Subanalysis of separate locations demonstrates significant benefit in the lower oesophagus, demonstrating potential benefit in Barrett's surveillance procedures. Disclosure of interest: None Declared.